Integrated process design and control methodology for heat exchanger network - Abu Bakar, Suraya Hanim (2015)
This paper explains about methodology framework development for integrated process design and control (IPDC) of heat exchanger network (HEN). In most of the IPDC HEN problems, the feasible solutions to the problems may lie in a relatively small portion of the search space due to the large number of variables and constraints involved. The ability to solve such problems depends on the effectiveness of the method of solution in identifying and locating the feasible solutions. Hence, one approach to solve this IPDC HEN problem is to apply a decomposition method. The method starts with defining the IPDC HEN problems and formulated as a mathematical programming. The IPDC HEN problem is decomposed into four hierarchical sequential stages: (i) target selection, (ii) HEN design analysis, (iii) controllability analysis, and (iv) optimal selection and verification. This method simultaneously combines the solution for both process design and process control problem by selecting a manipulated variable that represent both process design and process control which is minimum allowable temperature difference, ΔTmin. The decision on selection ΔTmin are guided by a new propose Trade-off plot that combine process design criteria and steady state process control criteria. A simple case study are used to demonstrate the methodology framework. The result shows that HEN with large ΔTmin is more flexible and easy to operate.